TCR/pMHC Interaction: Phenotypic Model for an Unsolved Enigma - Gálvez, Jesús; Gálvez, Juan J.; García-Peñarrubia, Pilar (Frontiers in Immunology, 2016)
TCR-pMHC interaction is the keystone of the adaptive immune response. This process exhibits an impressive capacity of speed, sensitivity and discrimination that allows to detect foreign pMHCs at very low concentration among much more abundant self-pMHC ligands. However, and despite over three decades of intensive research, the mechanisms by which this remarkable discrimination and sensitivity is attained remain controversial. In kinetic proofreading mechanisms (KPR) an increase of specificity occurs by reducing the sensitivity. To overcome this difficulty more elaborate models including feedback processes or induced rebinding have been incorporated into the KPR scheme. Here a new approach based on the assumption that the proofreading chain behaves differently for foreign and self pMHCs has been integrated into a phenotypic model in which the complexes responsible for T cell activation stabilize (for foreign peptides), or weaken (for foreign peptides), resulting in a dramatic increase in sensitivity and specificity. Stabilization and destabilization of complexes may be caused by conformational changes, rebinding, or any other process leading to variations in the dissociation rate constants of the complexes transmitting the activation. The numerical solution and the analytical expression for the steady state response as a function of koff(i) (i=0,1,..,N, where C0, C1,..,CN are the complexes in the proofreading chain) are provided. The activation chain speeds up and larger increases in sensitivity and discrimination are obtained if the rate of activation along the proofreading chain increases for foreign pMHCs and decreases for self ligands. Experimental implications and comparison with current models are discussed.